Long‐term outcome of liver transplantation in childhood: A study of 20‐year survivors. Issue 7 (12th January 2018) - Martinelli, J.; Habes, D.; Majed, L.; Guettier, C.; Gonzalès, E.; Linglart, A.; Larue, C.; Furlan, V.; Pariente, D.; Baujard, C.; Branchereau, S.; Gauthier, F.; et al.
Abstract : We report the results of a study of survival, liver and kidney functions, and growth with a median follow‐up of 24 years following liver transplantation in childhood. From 1988 to 1993, 128 children underwent deceased donor liver transplantation (median age: 2.5 years). Twenty‐year patient and graft survival rates were 79% and 64%, respectively. Raised serum aminotransferase and/or γ‐glutamyl transferase activities were present in 42% of survivors after a single transplantation. Graft histology (35 patients) showed signs of chronic rejection in 11 and biliary obstruction in 5. Mean total fibrosis scores were 4.5/9 and 3/9 in patients with abnormal and normal serum liver tests, respectively. Glomerular filtration rate was <90 mL·min −1 in 35 survivors, including 4 in end‐stage renal disease who were undergoing dialysis or had undergone renal transplantation. Median final heights were 159 cm for women and 172 cm for men; final height was below the target height in 37 patients. Twenty‐year survival after childhood liver transplantation may be close to 80%, and final height is within the normal range for most patients. However, chronic kidney disease or altered liver biochemistries are present in over one third of patients, which is a matter of concern for the future. Abstract : Of 128 children who underwent liver transplantation between 1988 and 1993, 101 were alive 20 to 28 years later, including 10 who displayed stage 3 to 5 chronic kidney disease.